PELATIHAN PEMULASARAAN JENAZAH PEREMPUAN SEBAGAI STRATEGI PEMBERDAYAAN PEREMPUAN DI DESA KARANGMOJO MAGETAN - Binsa, Abdul Aziz; Rohman, Muhammad Abdur; Meilana, Putri Bibit; Mushtofa, Syahrul; Dzikriyya F. B., Ihda Zullaida; Wahyudi, Oky Bagus; Chandra W., Rengga Krishna; Wahidah, Anti Syahrotul; Ngabdulloh, Moh Riza; Khunaifa, Naimul; Nurfajria, Rena; Hidayatulloh, Ahmad Aris; Awalia, Nila Hani; Awandar, Tia Anhar Setio (Abdimas IAI Ngawi, 2025)
Corpse care (pemulasaraan jenazah) is a collective obligation (fardhu kifayah) in Islam, encompassing bathing, shrouding, praying, and burying the deceased. However, in community practice, this duty is often entirely delegated to male funeral attendants (modin), even for female corpses, limiting community participation and understanding, especially among women. This community service project aimed to empower women by training them on the procedures for female corpse care in accordance with Islamic law. The implementation method consisted of four stages: (1) preparation, (2) execution (theoretical material delivery and direct practice), (3) mentoring, and (4) evaluation. The participants were 35 mothers from the Family Welfare Empowerment (PKK) group in Karangmojo Village. The results showed high enthusiasm and participation from the attendees, reaching 90% of the target. Participants gained not only a comprehensive theoretical understanding of the laws and procedures of the "4M": Memandikan (bathing the deceased), Mengkafani (shrouding the deceased), Menshalatkan (performing the funeral prayer), and Mengkafani (burying the deceased) but also practical skills through simulation. It is concluded that this training successfully enhanced the capacity and readiness of the PKK mothers to serve as local resources who are prepared and skilled in performing the fardhu kifayah duty, while also strengthening the socio-religious role of women at the village level.   Abstrak: Pengurusan jenazah (pemulasaraan) merupakan kewajiban kolektif (fardhu kifayah) dalam Islam yang meliputi memandikan, mengafani, menyalatkan, dan menguburkan. Namun dalam praktiknya di masyarakat, tugas ini seringkali diserahkan sepenuhnya kepada modin (petugas pemakaman) laki-laki, termasuk untuk jenazah perempuan, sehingga partisipasi dan pemahaman masyarakat, khususnya perempuan, masih terbatas. Tujuan pengabdian ini adalah untuk memberdayakan perempuan melalui pelatihan tata cara pemulasaraan jenazah perempuan yang sesuai dengan syariat Islam. Metode pelaksanaan terdiri dari empat tahap: (1) persiapan, (2) pelaksanaan (penyampaian materi teoritis dan praktik langsung), (3) pendampingan, dan (4) evaluasi. Peserta berjumlah 35 orang ibu-ibu PKK Desa Karangmojo. Hasil kegiatan menunjukkan antusiasme dan partisipasi yang tinggi dari peserta, mencapai 90% dari target. Peserta tidak hanya mendapatkan pemahaman teoritis yang komprehensif mengenai hukum dan tata cara 4M: Memandikan, Mengkafani, Menshalatkan, dan Menguburkan, tetapi juga keterampilan praktis melalui simulasi. Dapat disimpulkan bahwa pelatihan ini berhasil meningkatkan kapasitas dan kesiapan ibu-ibu PKK sebagai sumber daya lokal yang sigap dan terampil dalam melaksanakan kewajiban fardhu kifayah, sekaligus memperkuat peran sosial-keagamaan perempuan di tingkat desa. Kata Kunci: Pemulasaraan Jenazah, Fardhu Kifayah, Pemberdayaan Perempuan, Desa Karangmojo, Pelatihan